Possibility of Worsening Flow Diversion Effect Due to Morphological Changes of a Stented Artery With Multiple Overlapping Stents for Partially Thrombosed Vertebral Artery Aneurysms - Suzuki, Tomoaki; Hasegawa, Hitoshi; Ando, Kazuhiro; Shibuya, Kouhei; Takahashi, Haruhiko; Saito, Shoji; Oishi, Makoto; Fujii, Yukihiko (Frontiers in Neurology, 2020)
Background: Morphological changes of a stented artery can cause a flow diversion effect to reduce intra-aneurysmal flow; however, there is a potential for the negative effect of increased intra-aneurysmal flow. We present cases with multiple overlapping stents for a partially thrombosed vertebral artery aneurysm and characterize the hemodynamic properties of a recurrent case by focusing on the morphological changes of the stented artery. Methods: Between October 2017 and April 2019, four consecutive cases of symptomatic unruptured large and giant partially thrombosed vertebral artery aneurysms were treated with multiple overlapping low-profile visualized intraluminal support stents and no coils. Both angiographic and clinical outcomes were assessed. Computational fluid dynamics analysis was performed to clarify hemodynamic features. The degree of pressure elevation was calculated as the pressure difference (Pd). Wall shear stress (WSS) was also calculated. Results: In three of the four cases, successful flow reduction was achieved with no morphological change of the stented arteries. The patients’ symptoms were gradually improved. The remaining case required additional stents after the initial treatment. In the recurrent case, Pd was noticeably elevated at the aneurysm neck after treatment, and WSS was generally increased in the area due to altered blood flow into the aneurysm dome caused by morphological changes of the stented artery. Conclusion: Overlapping stents can be used for the treatment of large and giant thrombosed vertebral artery aneurysms with flow diversion effect; however, morphological changes of the stented artery requires careful attention as it may lead to an increase in the intra-aneurysmal flow, causing negative outcomes.